Asymmetric Catalytic N-Phosphonyl Imine Chemistry: the Use of Primary Free Amino Acids and Et(2)AlCN for Asymmetric Catalytic Strecker Reaction - Kaur, Parminder (2010)
The new asymmetric catalytic Strecker reaction of achiral N-phosphonyl imines has been established. Excellent enantioselectivity (95.2–99.7%ee) and yields (89–97%) have been achieved by using primary free natural amino acids as catalysts and Et(2)AlCN as nucleophile. This work also presents the novel use of non-volatile and inexpensive Et(2)AlCN in asymmetric catalysis. The N-phosphonyl protecting group enabled simple product purification to be achieved simply by washing the crude products with hexane. It can also be readily cleaved and recycled under mild condition to give a quantitative recovery of N,N′-bis(naphthalen-1-ylmethyl)ethane-1,2-diamine. A new mechanism was proposed for this reaction and was supported by experimental observations.